The greater Ramayana - Raghavan, V. (Venkatarama), 1908-1979 (Prof. L. Venkataratnam lectures, 1973)
Lectures delivered at the University of Madras on the influence of the Rāmāyaṇa on the Mahābhārata, Harivaṃśa, Purāṇas, and Upapurāṇas.